Variation in Protein, Carbohydrate and Lipid Content in the Body Wall of Commercial Sea Cucumber Holothuria spinifera (Theel, 1886) in Relation to Reproductive Stages - Asha, P. S.; Muthiah, P. (Fishery Technology, 2018)
The dry body wall from sea cucumbers, is ‘beche-demer’, is an important item of trade in the developing countries in the Indo-Pacific region. A study was conducted to assess the variation in biochemical constituents of the body wall of commercial sea cucumber Holothuria spinifera concerning the reproductive stages. The body wall of sea cucumbers belong to eight reproductive stages were pooled and dried in hot air oven at 80oC for 48 h. Standard procedures estimated the protein, total carbohydrate and total lipids. The mean values of proteins, carbohydrate and lipid content in the body wall of H. spinifera were 17.2, 2.8 and 1.3%, respectively. The highest concentration of these organic constituents during the maturing stages, decline during the postspawning periods indicating their role as the source of energy during gametogenesis. The one-way ANOVA on the differences in the mean protein, carbohydrate and lipid content in the body wall to the reproductive stages indicated a high level of significance (p<0.001).